The Relationship Between Activity Daily Living Level And Quality Of Life Of Geriatric Patients In RSUP Dr. Mohammad Hoesin Palembang - Angela Maria Linata; Jalalin (Sriwijaya Journal of Medicine, 2020)
Background The quality of life of the elderly is influenced by several factors such as physical health, psychological health, and good social relationships. Physical health is related to daily living activities that a person does in his daily life including ambulation, eating, dressing, bathing, brushing teeth and making up. At old age, a person will experience a decrease in physical condition which will affect the value of fulfilling one's daily living activities. This study aims to analyze the relationship between the level of independence of daily living activities and the level of quality of life of geriatric patients. Methods: This study was an observational analytic study with a cross sectional design. The samples were geriatric patients in Dr. Mohammad Hoesin Palembang in September-October 2019. The sample of this study was 55 respondents. Results: From 55 Geriatric patients in Dr. Mohammad Hoesin Palembang found 60% male respondents and 40% female respondents, the 60-74 years age group as much as 74.5%, the 75-90 year age group as much as 25.5%, the 50-60 year age group as much as 26%. Chi-square test results showed a significant relationship between the level of Activity Daily Living and the level of quality of life of geriatric patients (p value = 0.000). The results of the odds ratio in geriatric patients state that the probability of improving the quality of life is 27.7 times greater in patients who have an independent daily living activity level than in patients who have a total dependent daily living activity level. In the analysis, it was also found that the level of daily living activity of geriatric patients is a protective factor for the quality of life of geriatric patients. (95% CI = 0.006-0.206). Conclusion: There is a significant relationship between the level of daily living activity and the quality of life of geriatric patients in , dr. Mohammad Hoesin Palembang.